2016
DOI: 10.5465/amj.2013.1009
|View full text |Cite
|
Sign up to set email alerts
|

My Family Made Me Do It: A Cross-Domain, Self-Regulatory Perspective on Antecedents to Abusive Supervision

Abstract: Drawing on resource drain theory, we introduce self-regulatory resource (ego) depletion stemming from family-to-work conflict (FWC) as an alternative theoretical perspective on why supervisors behave abusively toward subordinates. Our two-study examination of a cross-domain antecedent of abusive supervision stands in contrast to prior research, which has focused primarily on work-related factors that influence abusive supervision. Further, our investigation shows how ego depletion is proximally related to abus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
228
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(238 citation statements)
references
References 92 publications
7
228
2
1
Order By: Relevance
“…First, from a conceptual perspective, we have shown the importance of considering how different manifestations of family‐generated resource depletion impact different manifestations of destructive leadership. Whereas previous research has investigated how ego depletion can negatively affect leaders' behaviour (i.e., Byrne et al, ; Courtwright et al, ), our study highlights both the affective and cognitive toll that multiple family‐based stressors can take on leadership. In so doing, we extend the body of research showing the widespread effects of the intersection of work and family more generally, and the non‐work influences on destructive leadership in particular.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…First, from a conceptual perspective, we have shown the importance of considering how different manifestations of family‐generated resource depletion impact different manifestations of destructive leadership. Whereas previous research has investigated how ego depletion can negatively affect leaders' behaviour (i.e., Byrne et al, ; Courtwright et al, ), our study highlights both the affective and cognitive toll that multiple family‐based stressors can take on leadership. In so doing, we extend the body of research showing the widespread effects of the intersection of work and family more generally, and the non‐work influences on destructive leadership in particular.…”
Section: Discussioncontrasting
confidence: 57%
“…More recently, emotional labour arising from dealing with customers was shown to deplete leaders' state self‐control, which then predicted abusive supervision (Yam, Fehr, Keng‐Highberger, Klotz, & Reynolds, ). Only Courtwright et al () studied the effects of family‐to‐work conflict on abusive supervision, and their second study showed that leaders who experience family‐to‐work conflict display more abusive behaviours toward subordinates via ego depletion. Thus, when taken together, we predict that in eroding the affective resources of leaders, family‐to‐work and romantic relationship conflict will result in the enactment of abusive supervisory behaviour.Hypothesis Leaders' depressive symptoms will mediate the relationship between family‐to‐work conflict and abusive supervision.Hypothesis Leaders' depressive symptoms will mediate the relationship between romantic relationship conflict and abusive supervision.…”
Section: Introductionmentioning
confidence: 99%
“…We stamped a unique code on each questionnaire to match the responses received from the two phases and the two sources. After we matched the responses, handled missing data, and excluded groups that had fewer than two employees (Courtright, Gardner, Smith, McCormick, & Colbert, ), the final sample consisted of 259 employees nested within 89 stores.…”
Section: Methodsmentioning
confidence: 99%
“…An important explanatory approach has highlighted supervisors' resource deficits as a critical antecedent, such that abusive supervision may occur more frequently if a supervisor lacks the capacity to effectively inhibit, override, or refrain from acting upon behavioral impulses (Wang, Sinclair, & Deese, ). Accordingly, scholars have linked indicators of resource deprivation (i.e., depressive symptoms, anxiety, and workplace alcohol consumption, Byrne et al, , as well as ego depletion, Courtright, Gardner, Smith, McCormick, & Colbert, ; Joosten, van Dijke, van Hiel, & De Cremer, ) with supervisors' abusive and deviant acts. When one extrapolates from these findings, it seems plausible to conceptualize abusive supervision as a supervisor's reaction to experiences of work stress and excessive job demands, such that supervisors are more likely to exhibit abusive behavior if they are emotionally exhausted from their work.…”
Section: Introductionmentioning
confidence: 99%